Analisis Kepuasan Pasien Terhadap Pelayanan Kesehatan di RSUD Lahat Tahun 2021 - Beti Hariani; Arie Wahyudi; Hamyatri Rawalilah (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
Satisfaction is the response or level of feeling of the patient obtained after the patient receives a health service product by comparing the perceived performance or result with the patient's needs and expectations. This study aims to analyze patient satisfaction with health services at Lahat Hospital in 2021. This study was a quantitative study with a cross sectional approach. The sampling technique used stratified random sampling obtained a sample of 97 respondents. Data was collected using a questionnaire, then the data was analyzed using the chi square test with a significance level of p value <0.05. The data were also analyzed using logistic regression test to determine the dominant variables that affect patient satisfaction. The results of the Community Satisfaction Index (IKM) in the Outpatient Lahat Hospital in 2021 were 77.44 with a service quality of